Biocontrol potential of lipopeptides produced by the novel Bacillus subtilis strain Y17B against postharvest Alternaria fruit rot of cherry - Ahmad, Tanvir; Xing, Fuguo; Nie, Chengrong; Cao, Changyu; Xiao, Ying; Yu, Xi; Moosa, Anam; Liu, Yang (Frontiers in Microbiology, 2023)
The use of synthetic fungicides against postharvest Alternaria rot adversely affects human health and the environment. In this study, as a safe alternative to fungicides, Bacillus subtilis strain Y17B isolated from soil exhibited significant antifungal activity against Alternaria alternata. Y17B was identified as B. subtilis based on phenotypic identification and 16S rRNA sequence analysis. To reveal the antimicrobial activity of this strain, a PCR-based study detected the presence of antifungal lipopeptide (LP) biosynthetic genes from genomic DNA. UPLC Q TOF mass spectrometry analysis detected the LPs surfactin (m/z 994.64, 1022.68, and 1026.62), iturin (m/z 1043.56), and fengycin (m/z 1491.85) in the extracted LP crude of B. subtilis Y17B. In vitro antagonistic study demonstrated the efficiency of LPs in inhibiting A. alternata growth. Microscopy (SEM and TEM) studies showed the alteration of the morphology of A. alternata in the interaction with LPs. In vivo test results revealed the efficiency of LPs in reducing the growth of the A. alternata pathogen. The overall results highlight the biocontrol potential of LPs produced by B. subtilis Y17B as an effective biological control agent against A. alternata fruit rot of cherry.